2020
DOI: 10.1073/pnas.1914794117
|View full text |Cite
|
Sign up to set email alerts
|

Environmental reservoir dynamics predict global infection patterns and population impacts for the fungal disease white-nose syndrome

Abstract: Disease outbreaks and pathogen introductions can have significant effects on host populations, and the ability of pathogens to persist in the environment can exacerbate disease impacts by fueling sustained transmission, seasonal epidemics, and repeated spillover events. While theory suggests that the presence of an environmental reservoir increases the risk of host declines and threat of extinction, the influence of reservoir dynamics on transmission and population impacts remains poorly described. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
167
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(179 citation statements)
references
References 44 publications
(64 reference statements)
6
167
0
Order By: Relevance
“…Indeed, contact of bats with the contaminated environment (Linder et al 2011;Lorch et al 2013aLorch et al , 2013b in autumn has been shown to initiate the infection (Langwig et al 2015). Our findings further complement recent findings suggesting that persistence of high levels P. destructans in the environment result in widespread infections (Hoyt et al 2020). Although the primary method of spread of P. destructans and WNS is bat-to-bat (Raudabaugh & Miller 2013), under our parameter set only 1 in 10 is due to direct contact to an infectious individual during hibernation.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, contact of bats with the contaminated environment (Linder et al 2011;Lorch et al 2013aLorch et al , 2013b in autumn has been shown to initiate the infection (Langwig et al 2015). Our findings further complement recent findings suggesting that persistence of high levels P. destructans in the environment result in widespread infections (Hoyt et al 2020). Although the primary method of spread of P. destructans and WNS is bat-to-bat (Raudabaugh & Miller 2013), under our parameter set only 1 in 10 is due to direct contact to an infectious individual during hibernation.…”
Section: Discussionsupporting
confidence: 88%
“…The devastating impact of WNS on a diverse group of North American bats likely resulted from evolutionary isolation of the continent's bat fauna from other parts of the world for millions of years, despite other species of Pseudogymnoascus being present. Bats in both Europe and Asia can become infected by P. destructans but do not suffer mass mortality from WNS [36,37]. The bat fauna spanning the higher latitudes of North America (in the US and Canada) is composed almost entirely of endemic species belonging to the family Vespertilionidae.…”
Section: Lessons From An Epizootic-susceptibility Of North American Bmentioning
confidence: 99%
“…Bats in both Europe and Asia can become infected by P . destructans but do not suffer mass mortality from WNS [ 36 , 37 ]. The bat fauna spanning the higher latitudes of North America (in the US and Canada) is composed almost entirely of endemic species belonging to the family Vespertilionidae.…”
Section: Lessons From An Epizootic—susceptibility Of North American Bmentioning
confidence: 99%
“…The presence and types of fomites can influence dispersal of pathogens and disease dynamics 18 , 19 . Therefore, the role of substrates is significant in situations where viable pathogens from an environmental substrate can re-infect hosts or remain as an environmental reservoir 20 – 22 . Understanding the growth and survival of pathogens on environmental substrates is critical to inform management interventions that might sanitize or modify structures to reduce transmission risk 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%